Public policies on sustainable flood risk management: Study cases of the Netherlands and Malawi - Maulana, Precious Douglas; Koestoer, Raldi Hendrotoro Seputro; Karuniasa, Mahawan (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This study compares flood management strategies in Malawi and the Netherlands, emphasizing their respective advantages and disadvantages. The Netherlands is renowned globally for its flood defense, prioritizing prevention, stakeholder involvement, and nature-based solutions through sophisticated infrastructure and proactive approaches. However, future challenges may arise from economic expansion and climate change pressures. In contrast, Malawi, despite having fewer resources, is making strides with its National Resilience Strategy, focusing on risk mitigation, sustainable agriculture, and early warning systems to combat flooding and hunger vulnerabilities. Yet, it faces significant issues with financing, management, and the long-term sustainability of community-based projects. Methods: This study utilized bibliometric analysis and a Systematic Literature Review (SLR), employing a comparative approach to evaluate Malawian and Dutch public policies on flooding disasters. The aim was to identify similarities and differences in their approaches to flood risk management. Findings: The Netherlands’ proactive flood management strategy, characterized by advanced infrastructure and integrated policy frameworks, is a model for high-capacity settings. Its emphasis on nature-based solutions and stakeholder engagement further strengthens its resilience. Malawi's approach, while resource-constrained, shows promise through its National Resilience Strategy, which targets risk reduction, sustainable agricultural practices, and robust early warning systems. Nevertheless, Malawi continues to grapple with financing, effective management, and the sustainability of its flood risk mitigation initiatives. Conclusion: The experiences of the Netherlands and Malawi illustrate the need for continuous policy adaptation and the challenges of managing flood risks in diverse socioeconomic contexts. This research clarifies the relative benefits of different flood control strategies and emphasizes the importance of tailored approaches to address the complexities of flood dangers. Both countries demonstrate the ongoing need for regulatory reform to enhance flood risk mitigation efforts. Novelty/Originality of this Study: This study uniquely compares the flood risk management policies of Malawi and the Netherlands, highlighting the differences between a developing nation's reactive, community-focused approach and a developed country's proactive, infrastructure-intensive strategy. By analyzing their respective strengths and weaknesses, it identifies potential improvements and opportunities for both nations to enhance their flood management and resilience.